2003
DOI: 10.3136/fstr.9.392
|View full text |Cite
|
Sign up to set email alerts
|

.ALPHA.-Glucosidase Inhibitory Activity in Leaves of Some Mulberry Varieties

Abstract: The seasonal and polyploidal changes of ␣-glucosidase (rat-intestinal) inhibitory activity in mulberry leaves were compared in 12 mulberry varieties. Enashi, Fusoumaru, No. 325 and Kenmochi which are classified as 3 major varieties in Japan were harvested in May or August as the field samples. Shimaguwa and the 3 different wild types such as Kuromiguwa, Nagamiguwa, Midoriguwa were harvested in May as the greenhouse samples. Some varieties harvested in the field or greenhouse indicated a difference in ␣-glucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
0
14
1
1
Order By: Relevance
“…[8][9][10][11] Yatsunami et al have reported the relationship between the -glucosidase inhibitory activity and 1-DNJ concentration from a group of species, 10) but not enough is known about -glucosidase inhibitors other than 1-DNJ from each cultivar. Since the -glucosidase inhibitory activity was not consistent with the 1-DNJ concentration in several cultivars, it is thought that -glucosidase inhibitors besides 1-DNJ were involved in the effective defense by mulberry plants against insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Yatsunami et al have reported the relationship between the -glucosidase inhibitory activity and 1-DNJ concentration from a group of species, 10) but not enough is known about -glucosidase inhibitors other than 1-DNJ from each cultivar. Since the -glucosidase inhibitory activity was not consistent with the 1-DNJ concentration in several cultivars, it is thought that -glucosidase inhibitors besides 1-DNJ were involved in the effective defense by mulberry plants against insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…The typical cultivars of mulberry plants are maintained and administered in Japan at the National Institute of Agrobiological Sciences (Tsukuba, Ibaraki, Japan) and the Experimental Farm of Textile Science and Technology of Shinshu University (Ueda, Nagano, Japan). It has been reported that the -glucosidase inhibitory activity and 1-DNJ concentration of mulberry leaves differ among various cultivars and seasons, [8][9][10][11] but it is unknown which environmental conditions influence the -glucosidase inhibitory activity. We therefore investigated in this study the relationship between the environmental conditions and -glucosidase inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in a-glucosidase inhibitory activity in Morus leaves were previously observed in association with polyploidy of the same variety [1]. An active component of Morus leaves, 1-deoxynojirimycin (DNJ), is known to be a strong intestinal a-glucosidase inhibitor [2,3].…”
Section: Introductionmentioning
confidence: 95%
“…This test was designed to investigate the maltase inhibitory There are a number of reports about the antihyperglycemic effects of natural resources such as Morus alba, Rosa damascena, Lonicera japonica, and Ganoderma lucidum (Yatsunami et al, 2003;Naowaboot et al, 2009;Gholamhoseinian et al, 2009;Zhang et al, 2013;Usui et al, 2007). AFS60 showed 15%…”
Section: α-Glucosidase Inhibition and Antihyperglycemic Effects Of Amentioning
confidence: 99%